Numerical Study on Flow Field Characteristics of Wind Turbine with Double Fork Tip Structure - Yuanjun Dai, Mingcheng Zhai, Kai He, (Design Engineering, 2020)
Based on the double fork tip structure of wing of Boeing 737MAX, herein, we designed a new type of wind turbine with double fork tip structure blade. By the means of computational fluid dynamics method, fork we simulated wind turbine with original tip structure and two type of double fork tip structures; wind velocity was set at 10 m/s, tip velocity ratio was 4.5, and the effect of wind turbine fluid field from different tip structure were investigated. The results show that double fork tip structure was able to increase the pressure difference between pressure surface and suction surface by 4.3% and 7.7%, comparing with the original tip structure; as a result, the rotor power coefficient was increased. The double fork tip structure increased the linear velocity and velocity gradient of the blade tip, the linear velocity was increased by 3.5% and 4.3% comparing with original tip blade. The wake and tip vortex of double fork tip structure wind turbine tend to move inward, the tendency increases with a smaller angle.